1993
DOI: 10.1002/1098-108x(199307)14:1<1::aid-eat2260140102>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent overeating: An empirical comparison of binge eating disorder, bulimia nervosa, and obesity

Abstract: The goal of the study was to contribute empirical data to the discussion of appropriate diagnostic classification of obese and nonobese, hinging, and nonbinging eating disordered patients. The study consists of two parts: (1) patients with binge eating disorder (BED) (N = 22) are compared to a matched sample of patients with bulimia nervosa (BN) and to 16 patients with obesity (body mass index [BMI] >30). These patient groups were crosssectionally assessed using expert ratings (interview) and self‐ratings. (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 27 publications
8
53
0
Order By: Relevance
“…Eldredge and Agras (46) also found similar age at first overweight episode in individuals with BED, Eating Disorders Not Otherwise Specified, or without eating disorder. But, in other studies, individuals with BED reported first being overweight at an earlier age than those without BED (8,21).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Eldredge and Agras (46) also found similar age at first overweight episode in individuals with BED, Eating Disorders Not Otherwise Specified, or without eating disorder. But, in other studies, individuals with BED reported first being overweight at an earlier age than those without BED (8,21).…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have also demonstrated that obese individuals with BED present more psychopathology, particularly depressive symptoms, than non-bingeing obese individuals (21)(22)(23). Alexithymia, known as difficulties in identifying, understanding, and verbalizing emotional states (24), may be another distinctive feature of this subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experience, however, indicates that a substantial number of those who present for treatment of an eating disorder do not fulfil diagnostic criteria for either of these disorders (Mitchell et al 1986; Bunnell et al 1990;Hall & Hay, 1991). A particularly common group are those who have recurrent episodes of uncontrolled over-eating ('binges') yet do not have bulimia nervosa (Clinton & Giant, 1992;Fichter et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, obese participants with BED reported elevated levels of preoccupation with thinness on the ED1 and EDI-2 (22), but did not differ from obese non-binge eating participants on body dissatisfaction ratings (16,32). No differences were detected on either of these ED1 subscales in a cross-sectional study comparing BED participants to obese participants (19). In a comparison of obese women seeking weight loss treatment, severity of binge eating was found to correlate with drive for thinness but not body dissatisfaction (35).…”
Section: Introductionmentioning
confidence: 99%